Adaption of neurosurgical resection patterns for pediatric low-grade glioma spanning two decades - report from the German LGG-studies 1996-2018 - Kelety, Tibor; Thomale, Ulrich-Wilhelm; Kandels, Daniela; Schuhmann, Martin U.; El Damaty, Ahmed; Krauss, Jürgen; Frühwald, Michael; Driever, Pablo Hernáiz; Witt, Olaf; Bison, Brigitte; Warmuth-Metz, Monika; Pietsch, Torsten; et al. (Cancer medicine, 2024)
Introduction Neurosurgery is considered the mainstay of treatment for pediatric low-grade glioma (LGG); the extent of resection determines subsequent stratification in current treatment protocols. Yet, surgical radicality must be balanced against the risks of complications that may affect long-term quality of life. We investigated whether this consideration impacted surgical resection patterns over time for patients of the German LGG studies. Patients and Methods Four thousand two hundred and seventy pediatric patients from three successive LGG studies (median age at diagnosis 7.6 years, neurofibromatosis (NF1) 14.7%) were grouped into 5 consecutive time intervals (TI1-5) for date of diagnosis and analyzed for timing and extent of first surgery with respect to tumor site, histology, NF1-status, sex, and age. Results The fraction of radiological LGG diagnoses increased over time (TI1 12.6%; TI5 21.7%), while the extent of the first neurosurgical intervention (3440/4270) showed a reduced fraction of complete/subtotal and an increase of partial resections from TI1 to TI5. Binary logistic regression analysis for the first intervention within the first year following diagnosis confirmed the temporal trends (p < 0.001) and the link with tumor site for each extent of resection (p < 0.001). Higher age is related to more complete resections in the cerebellum and cerebral hemispheres. Conclusions The declining extent of surgical resections over time was unrelated to patient characteristics. It paralleled the evolution of comprehensive treatment algorithms; thus, it may reflect alignment of surgical practice to recommendations in respect to age, tumor site, and NF1-status integrated as such into current treatment guidelines. Further investigations are needed to understand how planning, performance, or tumor characteristics impact achieving surgical goals.